PAUL'S THOUGHTS ON SLAVERY IN THE PERSPECTIVE OF RAMBU SOLO’' TRADITIONAL CEREMONIES IN TORAJA - Eunike Eunike; Agus Nuria (Anfa Mediatama, 2023)
This research shows an understanding of Paul's views on liberation from slavery in the context of the Rambu Solo’ Traditional Ceremony in Toraja. The background illustrates the changes in Torajan culture and the values embodied in Rambu Solo’'. The focus of the research is to understand how Paul's teaching on freedom from slavery can be applied to the practice of slavery in Torajan culture. Qualitative methods are used through data collection from literature review and in-depth analysis. The results show the relevance of the values emphasized by Paul in evaluating the practice of slavery in Toraja, especially in the context of spiritual freedom and equality before God. The implications of Paul's teachings trigger deep reflection on the dynamics of social relations and cultural practices embodied in Torajan funeral ceremonies, highlighting the importance of understanding spiritual values in the context of local traditions.